The nonlinear relationship between estimated glomerular filtration rate and cardiovascular disease in US adults: a cross-sectional study from NHANES 2007–2018 - Zhou, Ce; Zhou, You; Shuai, Niannian; Zhou, Jiaxiu; Kuang, Xin (Frontiers in Cardiovascular Medicine, 2024)
Background and aimEstimated glomerular filtration rate (eGFR) is a key indicator of kidney function and is associated with numerous health conditions. This study examines the association between eGFR and cardiovascular disease (CVD) risk in a representative cohort of the US adult population.MethodsA cross-sectional analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. The study included 31,020 participants aged 20 years and older. The eGFR estimates were calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. CVD was defined as a self-reported physician's diagnosis of congestive heart failure, coronary heart disease, angina pectoris, myocardial infarction, or stroke. To assess the association between eGFR and CVD risk, the study employed weighted linear regression and generalized additive models.ResultsThe study revealed a significant non-linear inverse association between eGFR and CVD risk, with a threshold effect observed at 99.3 ml/min/1.73 m². Below this threshold, each 10-unit increase in eGFR was associated with a 13% decrease in the odds of CVD (OR: 0.87, 95% CI: 0.84–0.90, P < 0.001). Above this threshold, no significant association was found between eGFR and CVD risk (OR: 1.04, 95% CI: 0.90–1.20, P = 0.60), indicating that further increases in eGFR beyond this point were not associated with additional cardiovascular benefits. Subgroup analyses revealed significant interactions for eGFR categories, anemia status, and ratio of family income to poverty (PIR).ConclusionsThis study shows that there is a non-linear relationship between eGFR and CVD risk in the US adult population. The study found evidence of a threshold effect. These findings emphasize the importance of monitoring and managing CVD risk factors in individuals with reduced kidney function, especially those with eGFR values below the identified threshold. The relationship between eGFR and CVD risk varies across different subgroups, particularly in relation to eGFR categories, anemia status, and socioeconomic factors.The results provide valuable insights for developing targeted CVD prevention and treatment strategies based on kidney function status.